An ultra-wide temperature and high rate lithium titanate battery

By using bihulled lithium titanate-lithium lanthanum zirconium oxide composite hollow microspheres as the negative electrode material, the problem of lower specific capacity and poor rate performance of lithium titanate batteries during high current charging and discharge is solved, and good cycle performance in high rate and ultra-wide temperature domains is achieved.

CN115425189BActive Publication Date: 2025-04-15HUZHOU YONGXING LITHIUM BATTERY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210892878.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-27
Publication Date
2025-04-15
Estimated Expiration
2042-07-27

AI Technical Summary

Technical Problem

Lithium titanate batteries have a faster drop in their specific capacity during high current charging and discharging, and their rate performance is poor, which limits their application.

Method used

Bihulled lithium titanate-lithium lanthanum zirconium oxide composite hollow microspheres were used as the negative electrode material, and SiO2@lithium titanate@SiO2@LLZO microspheres were coated layer by layer, and the electron conductivity was enhanced through carbon coating.

Benefits of technology

The electronic conductivity and ionic conductivity of lithium titanate negative electrode material are significantly improved, the cycling performance of the battery at high magnifications, and the good charging and discharging performance is maintained in the ultra-wide temperature range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115425189B_ABST
    Figure CN115425189B_ABST
Patent Text Reader

Abstract

The invention discloses an ultra-wide temperature high-rate lithium titanate battery, comprising a positive electrode, a negative electrode and an electrolyte; the active material in the negative electrode is a double-shell lithium titanate-lithium lanthanum zirconium oxide composite hollow microsphere, and the preparation steps are: preparation of monodisperse SiO2 microspheres; preparation of SiO2@lithium titanate microspheres; preparation of SiO2@lithium titanate@SiO2 microspheres; preparation of SiO2@lithium titanate@SiO2@LLZO microspheres; one-time calcination; template removal; carbon coating. The invention adopts double-shell lithium titanate-lithium lanthanum zirconium oxide composite hollow microspheres as negative electrode materials, which can significantly improve the electronic conductivity and ionic conductivity of lithium titanate negative electrode materials, and obtain a lithium titanate battery that can be used in an ultra-wide temperature range and has good high-rate charge and discharge performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to an ultra-wide temperature and high rate lithium titanate battery. Background Art

[0002] Lithium-ion batteries have the characteristics of high energy density, long cycle life, no memory effect, and no pollution to the environment. They have been widely used in portable electronic devices and electric vehicles. At present, the most widely used negative electrode material for commercial lithium-ion batteries is graphite. However, during the charging and discharging process, the graphite negative electrode has a lower voltage platform. During the lithium insertion and extraction process, lithium dendrites are easily formed on the negative electrode surface, which will puncture the battery separator, thus causing serious safety hazards such as short circuit. Safety issues are the key issues that lithium-ion batteries need to solve urgently.

[0003] Lithium titanate battery is Li4Ti5O 12 Lithium-ion battery as negative electrode. Li4Ti5O 12 The negative electrode material has the following advantages: 1. It has the "zero strain" characteristic that the skeleton structure hardly changes during the charge and discharge process, and has good cycle performance; 2. It has a high lithium potential (about 1.55V vs.Li / Li + ), it is not easy to form lithium dendrites, reducing the risk of internal short circuit; 3. It has fast charging and discharging characteristics (one order of magnitude higher than the diffusion coefficient of carbon) and high power density; 4. Its spinel structure has three-dimensional lithium ion diffusion channels, and no solid-liquid interface passivation film is formed on the surface. At low temperatures, various dynamic properties can still maintain the state at room temperature. Charging will not cause short circuits or lithium dendrites that deteriorate the negative electrode. Therefore, it has the ability to fully charge and discharge in an ultra-wide temperature range. Therefore, lithium titanate batteries have the ability to fully charge and discharge in an ultra-wide temperature range due to the negative electrode material Li4Ti5O 12 It has the characteristics of long cycle life, high safety, and wide temperature range. It has broad application prospects in the fields of power grid energy storage and new energy vehicles.

[0004] However, Li4Ti5O 12 The material's inherent conductivity is 10 -13 S / cm, the diffusion coefficient of lithium ions is about 10 -9 ~10 -13 cm 2 / s, poor electrical conductivity and low lithium ion diffusion make its specific capacity drop rapidly during high current charge and discharge, and its rate performance is poor, which limits its application. Summary of the invention

[0005] The present invention aims to overcome the problem that the specific capacity of lithium titanate batteries in the prior art decreases rapidly and the rate performance is poor during high-current charge and discharge. An ultra-wide temperature high-rate lithium titanate battery is provided. Double-shell lithium titanate-lithium lanthanum zirconium oxide composite hollow microspheres are used as negative electrode materials, which can significantly improve the electronic conductivity and ionic conductivity of the lithium titanate negative electrode material, thereby obtaining a lithium titanate battery that can be used in an ultra-wide temperature range and has good high-rate charge and discharge performance.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] An ultra-wide temperature and high rate lithium titanate battery comprises a positive electrode, a negative electrode and an electrolyte; the active material in the negative electrode is a double-shell lithium titanate-lithium lanthanum zirconium oxide composite hollow microsphere, and the preparation method comprises the following steps:

[0008] (1) Preparation of monodisperse SiO2 microspheres: under stirring, an anhydrous ethanol solution of ethyl orthosilicate is added dropwise to an anhydrous ethanol solution of ammonia water, and the reaction is stirred for 1 to 2 hours, and the product is separated to obtain monodisperse SiO2 microspheres;

[0009] (2) Preparation of SiO2@lithium titanate microspheres: Monodisperse SiO2 microspheres were added to anhydrous ethanol, and stearic acid was added. After uniform dispersion, tetrabutyl titanate was added. LiOH aqueous solution was added dropwise to the system under stirring, and the reaction was continued under stirring for 2 to 3 hours. The product was separated to obtain SiO2@lithium titanate microspheres.

[0010] (3) Preparation of SiO2@lithium titanate@SiO2 microspheres: SiO2@lithium titanate microspheres were added to anhydrous ethanol, and after being evenly dispersed, ethyl orthosilicate was added; anhydrous ethanol solution of ammonia water was added dropwise to the system under stirring, and the reaction was stirred for 1 to 2 hours, and the product was separated to obtain SiO2@lithium titanate@SiO2 microspheres;

[0011] (4) Preparation of SiO2@lithium titanate@SiO2@LLZO microspheres: LiNO3, La(NO3)3, and ZrO(NO3)2 were dissolved in deionized water, and SiO2@lithium titanate@SiO2 microspheres were added. After uniform dispersion, citric acid and ethylene glycol were added, and the mixture was stirred at 100-120°C for 12-24h to obtain SiO2@lithium titanate@SiO2@LLZO microspheres.

[0012] (5) primary calcination: calcining SiO2@lithium titanate@SiO2@LLZO microspheres at 700-900°C for 4-6 hours under an inert atmosphere to obtain a primary calcined material;

[0013] (6) Removing the template: After the pre-sintered material is cooled, it is added into a sodium hydroxide solution, stirred and reacted at 80-90° C. for 4-6 hours, and the product is separated, washed, and dried to obtain double-shell hollow microspheres;

[0014] (7) Carbon coating: After the double-shell hollow microspheres are mixed with glucose and ball-milled, they are subjected to secondary calcination in an inert atmosphere at a calcination temperature of 700 to 900° C. for 5 to 8 hours to obtain the double-shell lithium titanate-lithium lanthanum zirconium oxide composite hollow microspheres.

[0015] In the process of preparing the negative electrode material of the present invention, monodispersed SiO2 microspheres are used as cores, and SiO2@lithium titanate@SiO2@LLZO microspheres are obtained by layer-by-layer coating using a sol-gel method. After calcination, the SiO2 template layer is washed off with a sodium hydroxide solution to obtain double-shelled composite hollow microspheres; glucose is then used as a carbon source to carbon-coat the surface of the double-shelled hollow microspheres, and finally double-shelled lithium titanate-lithium lanthanum zirconium oxide composite hollow microspheres with a surface coated with a carbon coating layer are obtained. In the negative electrode material prepared by the present invention, the lithium titanate shell layer can enable the battery to have an ultra-wide operating temperature range (-50 to 80°C); the lithium lanthanum zirconium oxide (LLZO) shell layer is coated on the outside of the lithium titanate shell layer, which can improve the ionic conductivity of the lithium titanate negative electrode material, and the carbon coating layer coated on the outside of the double-shelled lithium titanate-lithium lanthanum zirconium oxide composite hollow microspheres can improve the electronic conductivity of the negative electrode material, thereby improving the battery's cycle performance at high rates.

[0016] The present application prepares the negative electrode material into double-shell hollow microspheres, which can increase the tap density of the lithium titanate negative electrode material, thereby increasing the energy density of the battery; and the hollow structure and the spacing between the lithium titanate shell and the LLZO shell can increase the specific surface area of ​​the negative electrode material, increase the permeability of the electrolyte and the contact area with the negative electrode material, provide more lithium ion transmission channels and lithium storage sites, thereby further increasing its conductivity and improving the battery's rate performance.

[0017] In the process of preparing SiO2@lithium titanate microspheres, stearic acid is added as a surfactant and a carbon source. On the one hand, during a calcination process, stearic acid is pyrolyzed to form a carbon layer coated on the surface of the lithium titanate shell layer, and the carbon coating layer coated on the surface of the LLZO shell layer improves the electronic conductivity of the negative electrode material together. On the other hand, the gas generated during the pyrolysis of stearic acid can increase the pore structure in the lithium titanate shell layer and the LLZO shell layer, which is beneficial to the removal of the SiO2 template and the increase of the contact area between the negative electrode material and the electrolyte, thereby improving the rate performance of the battery.

[0018] Preferably, the volume ratio of tetraethyl orthosilicate, ammonia water and anhydrous ethanol added in step (1) is 1:15-25:90-100.

[0019] Preferably, in step (2), the mass ratio of monodisperse SiO2 microspheres to tetrabutyl titanate is 1:8-10; the mass ratio of stearic acid to tetrabutyl titanate is 1:45-55; and the molar ratio of tetrabutyl titanate to LiOH is 5:4.2-4.6.

[0020] Preferably, in step (3), the mass ratio of SiO2@lithium titanate microspheres to tetraethyl orthosilicate is 1:3-5, and the volume ratio of tetraethyl orthosilicate to aqueous ammonia is 1:5-7.

[0021] Preferably, in step (4), the molar ratio of LiNO3, La(NO3)3 and ZrO(NO3)2 is 7.5-7.7:3:2; the ratio of the mass of the added SiO2@lithium titanate@SiO2 microspheres to the total mass of nitrate is 0.3-0.5:1; the ratio of the mass of citric acid and ethylene glycol to the total mass of nitrate is 1.2-1.5:0.8-1:1.

[0022] Preferably, the concentration of the sodium hydroxide solution in step (6) is 2 to 5 mol / L.

[0023] Preferably, in step (7), the mass ratio of double-shell hollow microspheres to glucose is 1:0.15-0.25, the ball milling medium is anhydrous ethanol, and the ball milling time is 2-4 hours.

[0024] Preferably, the active material in the positive electrode is selected from one or two of lithium iron manganese phosphate and NCM ternary materials.

[0025] Preferably, the electrolyte includes lithium salt and carbonate organic solvent.

[0026] Preferably, the concentration of lithium salt in the electrolyte is 1-2 mol / L.

[0027] Therefore, the present invention has the following beneficial effects:

[0028] (1) Using double-shell lithium titanate-lithium lanthanum zirconium oxide composite hollow microspheres as the active material of the negative electrode can improve the ionic conductivity and electronic conductivity of the lithium titanate negative electrode material and improve the cycle performance of the battery at high rates;

[0029] (2) Using double-shell lithium titanate-lithium lanthanum zirconium oxide composite hollow microspheres as the active material of the negative electrode can increase the tap density of the lithium titanate negative electrode material and improve the energy density of the battery;

[0030] (3) Coating the lithium titanate shell and the LLZO shell with a carbon layer can improve the electronic conductivity of the negative electrode material; at the same time, when stearic acid is used as a carbon source for pyrolysis, it can increase the pores in the lithium titanate shell and the LLZO shell, which is beneficial to increase the contact area between the negative electrode material and the electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 1 is the cycle curve of the battery in Example 1 at -20°C and 55°C.

[0032] Figure 2 : is the cycle curve of the battery in Example 2 at -20°C and 55°C.

[0033] Figure 3 : is the cycle curve of the battery in Example 3 at -20°C and 55°C. DETAILED DESCRIPTION

[0034] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments.

[0035] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art.

[0036] Embodiment 1:

[0037] An ultra-wide temperature high-rate lithium titanate button battery, comprising a positive electrode, a negative electrode and an electrolyte;

[0038] The components of the electrolyte are as follows: 1 mol / L LiPF6 is dissolved in a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC), and the mass ratio of EC, EMC and DMC in the mixed solvent is 1:1:1;

[0039] Positive electrode components: Active material LiMn 0.6 Fe 0.4 PO4, Super P, PVDF, the mass ratio is 93:4:3;

[0040] Negative electrode components: active material, Super P, PVDF, with a mass ratio of 95:2:3;

[0041] The active material in the negative electrode is a double-shell lithium titanate-lithium lanthanum zirconium oxide composite hollow microsphere, and the preparation method thereof is as follows:

[0042] (1) Preparation of monodisperse SiO2 microspheres: under stirring at 70 r / min, an anhydrous ethanol solution of tetraethyl orthosilicate was added dropwise to an anhydrous ethanol solution of ammonia water, the volume ratio of tetraethyl orthosilicate, ammonia water, and anhydrous ethanol being 1:20:96, and the stirring reaction was continued for 1.5 h, and the product was centrifuged to obtain monodisperse SiO2 microspheres;

[0043] (2) Preparation of SiO2@lithium titanate microspheres: monodisperse SiO2 microspheres were added to anhydrous ethanol, and stearic acid was added. After stirring and dispersing evenly, tetrabutyl titanate was added. LiOH aqueous solution was added dropwise to the system under stirring, and the stirring reaction was continued for 2.5 h. The product was centrifuged to obtain SiO2@lithium titanate microspheres. The mass ratio of monodisperse SiO2 microspheres to tetrabutyl titanate was 1:9, and the mass ratio of stearic acid to tetrabutyl titanate was 1:50. The molar ratio of tetrabutyl titanate to LiOH was 5:4.4.

[0044] (3) Preparation of SiO2@lithium titanate@SiO2 microspheres: SiO2@lithium titanate microspheres were added to anhydrous ethanol, and tetraethyl orthosilicate was added after uniform dispersion; anhydrous ethanol solution of ammonia water was added dropwise to the system under stirring, and the reaction was stirred for 1.5 h. The product was separated to obtain SiO2@lithium titanate@SiO2 microspheres; the mass ratio of SiO2@lithium titanate microspheres to tetraethyl orthosilicate was 1:4, and the volume ratio of tetraethyl orthosilicate to ammonia water was 1:6;

[0045] (4) Preparation of SiO2@lithium titanate@SiO2@LLZO microspheres: LiNO3, La(NO3)3, and ZrO(NO3)2 in a molar ratio of 7.6:3:2 were dissolved in deionized water, and SiO2@lithium titanate@SiO2 microspheres were added, and the ratio of the mass of SiO2@lithium titanate@SiO2 microspheres to the total mass of nitrate was 0.4:1; after uniform dispersion, citric acid and ethylene glycol were added, and the ratio of the mass of citric acid and ethylene glycol to the total mass of nitrate was 1.4:0.9:1, and the reaction was stirred at 110°C for 18 hours to obtain SiO2@lithium titanate@SiO2@LLZO microspheres;

[0046] (5) primary calcination: calcining SiO2@lithium titanate@SiO2@LLZO microspheres at 800°C for 5 h in an argon atmosphere to obtain a primary calcined material;

[0047] (6) Removing the template: After the pre-sintered material is cooled, it is added into a 3 mol / L sodium hydroxide solution and stirred at 90° C. for 5 h. The product is separated, washed and dried to obtain double-shell hollow microspheres;

[0048] (7) Carbon coating: The double-shelled hollow microspheres were mixed with glucose and ball-milled, the mass ratio of the double-shelled hollow microspheres to glucose was 1:0.2, the ball-milling medium was anhydrous ethanol, and the ball-milling time was 3 h; secondary calcination was carried out under argon atmosphere, the calcination temperature was 800° C., and the calcination time was 6 h to obtain the double-shelled lithium titanate-lithium lanthanum zirconium oxide composite hollow microspheres.

[0049] Embodiment 2:

[0050] An ultra-wide temperature high-rate lithium titanate button battery, comprising a positive electrode, a negative electrode and an electrolyte;

[0051] The components of the electrolyte are as follows: 1 mol / L LiPF6 is dissolved in a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC), and the mass ratio of EC, EMC and DMC in the mixed solvent is 1:1:1;

[0052] Positive electrode components: Active material LiMn 0.6 Fe 0.4 PO4, Super P, PVDF, the mass ratio is 90:4:3;

[0053] Negative electrode components: active material, Super P, PVDF, with a mass ratio of 90:2:3;

[0054] The active material in the negative electrode is a double-shell lithium titanate-lithium lanthanum zirconium oxide composite hollow microsphere, and the preparation method thereof is as follows:

[0055] (1) Preparation of monodisperse SiO2 microspheres: under stirring at 60 r / min, an anhydrous ethanol solution of tetraethyl orthosilicate was added dropwise to an anhydrous ethanol solution of ammonia water, the volume ratio of tetraethyl orthosilicate, ammonia water, and anhydrous ethanol being 1:15:90, and the reaction was continued by stirring for 1 h. The product was centrifuged to obtain monodisperse SiO2 microspheres;

[0056] (2) Preparation of SiO2@lithium titanate microspheres: monodisperse SiO2 microspheres were added to anhydrous ethanol, and stearic acid was added. After stirring and dispersing evenly, tetrabutyl titanate was added. LiOH aqueous solution was added dropwise to the system under stirring, and the stirring reaction was continued for 2 h. The product was centrifuged to obtain SiO2@lithium titanate microspheres. The mass ratio of monodisperse SiO2 microspheres to tetrabutyl titanate was 1:8, and the mass ratio of stearic acid to tetrabutyl titanate was 1:55. The molar ratio of tetrabutyl titanate to LiOH was 5:4.2.

[0057] (3) Preparation of SiO2@lithium titanate@SiO2 microspheres: SiO2@lithium titanate microspheres were added to anhydrous ethanol, and tetraethyl orthosilicate was added after uniform dispersion; anhydrous ethanol solution of ammonia water was added dropwise to the system under stirring, and the reaction was stirred for 1 h. The product was separated to obtain SiO2@lithium titanate@SiO2 microspheres; the mass ratio of SiO2@lithium titanate microspheres to tetraethyl orthosilicate was 1:3, and the volume ratio of tetraethyl orthosilicate to ammonia water was 1:5;

[0058] (4) Preparation of SiO2@lithium titanate@SiO2@LLZO microspheres: LiNO3, La(NO3)3, and ZrO(NO3)2 in a molar ratio of 7.5:3:2 were dissolved in deionized water, and SiO2@lithium titanate@SiO2 microspheres were added, and the ratio of the mass of SiO2@lithium titanate@SiO2 microspheres to the total mass of nitrate was 0.3:1; after uniform dispersion, citric acid and ethylene glycol were added, and the ratio of the mass of citric acid and ethylene glycol to the total mass of nitrate was 1.2:0.8:1, and the reaction was stirred at 100°C for 24 hours to obtain SiO2@lithium titanate@SiO2@LLZO microspheres;

[0059] (5) primary calcination: calcining SiO2@lithium titanate@SiO2@LLZO microspheres at 700°C for 6 h in an argon atmosphere to obtain a primary calcined material;

[0060] (6) Removing the template: After the pre-sintered material is cooled, it is added into a 2 mol / L sodium hydroxide solution and stirred at 90° C. for 6 h. The product is separated, washed and dried to obtain double-shell hollow microspheres;

[0061] (7) Carbon coating: The double-shelled hollow microspheres were mixed with glucose and ball-milled, the mass ratio of the double-shelled hollow microspheres to glucose was 1:0.15, the ball-milling medium was anhydrous ethanol, and the ball-milling time was 2 h; secondary calcination was carried out under argon atmosphere, the calcination temperature was 900° C., and the calcination time was 5 h to obtain the double-shelled lithium titanate-lithium lanthanum zirconium oxide composite hollow microspheres.

[0062] Embodiment 3:

[0063] An ultra-wide temperature high-rate lithium titanate button battery, comprising a positive electrode, a negative electrode and an electrolyte;

[0064] The components of the electrolyte are as follows: 2 mol / L LiPF6 is dissolved in a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC), and the mass ratio of EC, EMC and DMC in the mixed solvent is 1:1:1;

[0065] Positive electrode components: Active material LiMn 0.6 Fe 0.4 PO4, Super P, PVDF, the mass ratio is 93:4:3;

[0066] The components of the negative electrode: active material, Super P, PVDF, the mass ratio is 93:2:3;

[0067] The active material in the negative electrode is a double-shell lithium titanate-lithium lanthanum zirconium oxide composite hollow microsphere, and the preparation method thereof is as follows:

[0068] (1) Preparation of monodisperse SiO2 microspheres: under stirring at 80 r / min, an anhydrous ethanol solution of tetraethyl orthosilicate was added dropwise to an anhydrous ethanol solution of ammonia water, the volume ratio of tetraethyl orthosilicate, ammonia water, and anhydrous ethanol being 1:25:100, the stirring reaction was continued for 2 h, and the product was centrifuged to obtain monodisperse SiO2 microspheres;

[0069] (2) Preparation of SiO2@lithium titanate microspheres: monodisperse SiO2 microspheres were added to anhydrous ethanol, and stearic acid was added. After stirring and dispersing evenly, tetrabutyl titanate was added. LiOH aqueous solution was added dropwise to the system under stirring, and the stirring reaction was continued for 3 h. The product was centrifuged to obtain SiO2@lithium titanate microspheres. The mass ratio of monodisperse SiO2 microspheres to tetrabutyl titanate was 1:10, and the mass ratio of stearic acid to tetrabutyl titanate was 1:45. The molar ratio of tetrabutyl titanate to LiOH was 5:4.6.

[0070] (3) Preparation of SiO2@lithium titanate@SiO2 microspheres: SiO2@lithium titanate microspheres were added to anhydrous ethanol, and tetraethyl orthosilicate was added after uniform dispersion; anhydrous ethanol solution of ammonia water was added dropwise to the system under stirring, and the reaction was stirred for 1 h. The product was separated to obtain SiO2@lithium titanate@SiO2 microspheres; the mass ratio of SiO2@lithium titanate microspheres to tetraethyl orthosilicate was 1:5, and the volume ratio of tetraethyl orthosilicate to ammonia water was 1:7;

[0071] (4) Preparation of SiO2@lithium titanate@SiO2@LLZO microspheres: LiNO3, La(NO3)3, and ZrO(NO3)2 in a molar ratio of 7.7:3:2 were dissolved in deionized water, and SiO2@lithium titanate@SiO2 microspheres were added, and the ratio of the mass of SiO2@lithium titanate@SiO2 microspheres to the total mass of nitrate was 0.5:1; after uniform dispersion, citric acid and ethylene glycol were added, and the ratio of the mass of citric acid and ethylene glycol to the total mass of nitrate was 1.5:1:1, and the reaction was stirred at 120°C for 12 hours to obtain SiO2@lithium titanate@SiO2@LLZO microspheres;

[0072] (5) primary calcination: calcining SiO2@lithium titanate@SiO2@LLZO microspheres at 900°C for 4 h in an argon atmosphere to obtain a primary calcined material;

[0073] (6) Removing the template: After the pre-sintered material is cooled, it is added into a 5 mol / L sodium hydroxide solution and stirred at 80° C. for 4 h. The product is separated, washed and dried to obtain double-shell hollow microspheres;

[0074] (7) Carbon coating: The double-shelled hollow microspheres were mixed with glucose and ball-milled, the mass ratio of the double-shelled hollow microspheres to glucose was 1:0.25, the ball-milling medium was anhydrous ethanol, and the ball-milling time was 4 h; secondary calcination was carried out under argon atmosphere, the calcination temperature was 700° C., and the calcination time was 8 h to obtain the double-shelled lithium titanate-lithium lanthanum zirconium oxide composite hollow microspheres.

[0075] Comparative Example 1 (LLZO layer not provided):

[0076] In Comparative Example 1, the active material of the negative electrode is lithium titanate hollow microspheres, and the preparation method thereof is as follows:

[0077] (1) Preparation of monodisperse SiO2 microspheres: under stirring at 70 r / min, an anhydrous ethanol solution of tetraethyl orthosilicate was added dropwise to an anhydrous ethanol solution of ammonia water, the volume ratio of tetraethyl orthosilicate, ammonia water, and anhydrous ethanol being 1:20:96, and the stirring reaction was continued for 1.5 h, and the product was centrifuged to obtain monodisperse SiO2 microspheres;

[0078] (2) Preparation of SiO2@lithium titanate microspheres: monodisperse SiO2 microspheres were added to anhydrous ethanol, and stearic acid was added. After stirring and dispersing evenly, tetrabutyl titanate was added. LiOH aqueous solution was added dropwise to the system under stirring, and the stirring reaction was continued for 2.5 h. The product was centrifuged to obtain SiO2@lithium titanate microspheres. The mass ratio of monodisperse SiO2 microspheres to tetrabutyl titanate was 1:9, and the mass ratio of stearic acid to tetrabutyl titanate was 1:50. The molar ratio of tetrabutyl titanate to LiOH was 5:4.4.

[0079] (3) primary calcination: calcining SiO2@lithium titanate microspheres at 800°C for 5 h in an argon atmosphere to obtain a primary calcined material;

[0080] (4) Removing the template: After the pre-sintered material is cooled, it is added into a 3 mol / L sodium hydroxide solution, stirred and reacted at 90° C. for 5 h, and the product is separated, washed, and dried to obtain hollow microspheres;

[0081] (5) Carbon coating: the hollow microspheres were mixed with glucose and ball-milled, the mass ratio of the hollow microspheres to glucose was 1:0.2, the ball-milling medium was anhydrous ethanol, and the ball-milling time was 3 h; secondary calcination was performed under an argon atmosphere, the calcination temperature was 800° C., and the calcination time was 6 h to obtain the lithium titanate hollow microspheres;

[0082] The rest are the same as in Example 1.

[0083] Comparative Example 2 (no carbon coating layer):

[0084] In Comparative Example 2, the preparation method of the active material of the negative electrode is:

[0085] (1) Preparation of monodisperse SiO2 microspheres: under stirring at 70 r / min, an anhydrous ethanol solution of tetraethyl orthosilicate was added dropwise to an anhydrous ethanol solution of ammonia water, the volume ratio of tetraethyl orthosilicate, ammonia water, and anhydrous ethanol being 1:20:96, and the stirring reaction was continued for 1.5 h, and the product was centrifuged to obtain monodisperse SiO2 microspheres;

[0086] (2) Preparation of SiO2@lithium titanate microspheres: monodisperse SiO2 microspheres were added to anhydrous ethanol, and stearic acid was added. After stirring and dispersing evenly, tetrabutyl titanate was added. LiOH aqueous solution was added dropwise to the system under stirring, and the stirring reaction was continued for 2.5 h. The product was centrifuged to obtain SiO2@lithium titanate microspheres. The mass ratio of monodisperse SiO2 microspheres to tetrabutyl titanate was 1:9, and the mass ratio of stearic acid to tetrabutyl titanate was 1:50. The molar ratio of tetrabutyl titanate to LiOH was 5:4.4.

[0087] (3) Preparation of SiO2@lithium titanate@SiO2 microspheres: SiO2@lithium titanate microspheres were added to anhydrous ethanol, and tetraethyl orthosilicate was added after uniform dispersion; anhydrous ethanol solution of ammonia water was added dropwise to the system under stirring, and the reaction was stirred for 1.5 h. The product was separated to obtain SiO2@lithium titanate@SiO2 microspheres; the mass ratio of SiO2@lithium titanate microspheres to tetraethyl orthosilicate was 1:4, and the volume ratio of tetraethyl orthosilicate to ammonia water was 1:6;

[0088] (4) Preparation of SiO2@lithium titanate@SiO2@LLZO microspheres: LiNO3, La(NO3)3, and ZrO(NO3)2 in a molar ratio of 7.6:3:2 were dissolved in deionized water, and SiO2@lithium titanate@SiO2 microspheres were added, and the ratio of the mass of SiO2@lithium titanate@SiO2 microspheres to the total mass of nitrate was 0.4:1; after uniform dispersion, citric acid and ethylene glycol were added, and the ratio of the mass of citric acid and ethylene glycol to the total mass of nitrate was 1.4:0.9:1, and the reaction was stirred at 110°C for 18 hours to obtain SiO2@lithium titanate@SiO2@LLZO microspheres;

[0089] (5) primary calcination: calcining SiO2@lithium titanate@SiO2@LLZO microspheres at 800°C for 5 h in an argon atmosphere to obtain a primary calcined material;

[0090] (6) Removing the template: After the pre-sintered material is cooled, it is added into a 3 mol / L sodium hydroxide solution, stirred and reacted at 90° C. for 5 h, and the product is separated, washed, and dried to obtain the double-shell lithium titanate-lithium lanthanum zirconium oxide composite hollow microspheres;

[0091] The rest are the same as in Example 1.

[0092] Comparative Example 3 (without hollow structure):

[0093] In Comparative Example 3, the active material of the negative electrode is a lithium titanate-lithium lanthanum zirconium oxide composite, and the preparation method thereof is as follows:

[0094] (1) Preparation of lithium titanate: tetrabutyl titanate and stearic acid were added to anhydrous ethanol and stirred to dissolve; under stirring, a LiOH aqueous solution was added dropwise to the solution, and the stirring reaction was continued for 2 hours, and the product was centrifuged to obtain lithium titanate; the mass ratio of stearic acid to tetrabutyl titanate was 1:50; the molar ratio of tetrabutyl titanate to LiOH was 5:4.2;

[0095] (2) Preparation of lithium titanate @LLZO: LiNO3, La(NO3)3, and ZrO(NO3)2 in a molar ratio of 7.5:3:2 were dissolved in deionized water, and lithium titanate was added, and the ratio of the mass of lithium titanate to the total mass of nitrate was 0.3:1; after uniform dispersion, citric acid and ethylene glycol were added, and the ratio of the mass of citric acid and ethylene glycol to the total mass of nitrate was 1.2:0.8:1, and the reaction was stirred at 100°C for 24 hours to obtain lithium titanate @LLZO;

[0096] (3) Primary calcination: calcining the lithium titanate@LLZO microspheres at 700°C for 6 h in an argon atmosphere to obtain a primary calcined material;

[0097] (4) Carbon coating: the primary calcined material was mixed with glucose and ball-milled, the mass ratio of the primary calcined material to glucose was 1:0.15, the ball-milling medium was anhydrous ethanol, and the ball-milling time was 2 hours; secondary calcination was performed under an argon atmosphere, the calcination temperature was 900° C., and the calcination time was 5 hours to obtain the lithium titanate-lithium lanthanum zirconium oxide composite;

[0098] The rest are the same as in Example 1.

[0099] Comparative Example 4 (no space between lithium titanate shell layer and LLZO layer):

[0100] In Comparative Example 4, the negative electrode activity is modified by coating lithium lanthanum zirconium oxide with lithium titanate hollow microspheres, and the preparation method thereof is as follows:

[0101] (1) Preparation of monodisperse SiO2 microspheres: under stirring at 70 r / min, an anhydrous ethanol solution of tetraethyl orthosilicate was added dropwise to an anhydrous ethanol solution of ammonia water, the volume ratio of tetraethyl orthosilicate, ammonia water, and anhydrous ethanol being 1:20:96, and the stirring reaction was continued for 1.5 h, and the product was centrifuged to obtain monodisperse SiO2 microspheres;

[0102] (2) Preparation of SiO2@lithium titanate microspheres: monodisperse SiO2 microspheres were added to anhydrous ethanol, and stearic acid was added. After stirring and dispersing evenly, tetrabutyl titanate was added. LiOH aqueous solution was added dropwise to the system under stirring, and the stirring reaction was continued for 2.5 h. The product was centrifuged to obtain SiO2@lithium titanate microspheres. The mass ratio of monodisperse SiO2 microspheres to tetrabutyl titanate was 1:9, and the mass ratio of stearic acid to tetrabutyl titanate was 1:50. The molar ratio of tetrabutyl titanate to LiOH was 5:4.4.

[0103] (3) Preparation of SiO2@lithium titanate@LLZO microspheres: LiNO3, La(NO3)3, and ZrO(NO3)2 in a molar ratio of 7.6:3:2 were dissolved in deionized water, and SiO2@lithium titanate microspheres were added, and the ratio of the mass of SiO2@lithium titanate microspheres to the total mass of nitrate was 0.4:1; after uniform dispersion, citric acid and ethylene glycol were added, and the ratio of the mass of citric acid and ethylene glycol to the total mass of nitrate was 1.4:0.9:1, and the reaction was stirred at 110°C for 18 hours to obtain SiO2@lithium titanate@LLZO microspheres;

[0104] (4) primary calcination: calcining SiO2@lithium titanate@LLZO microspheres at 800°C for 5 h in an argon atmosphere to obtain a primary calcined material;

[0105] (5) Removing the template: After the pre-sintered material is cooled, it is added into a 3 mol / L sodium hydroxide solution, stirred and reacted at 90° C. for 5 h, and the product is separated, washed, and dried to obtain hollow microspheres;

[0106] (6) Carbon coating: The hollow microspheres were mixed with glucose and ball-milled, the mass ratio of the hollow microspheres to glucose was 1:0.2, the ball-milling medium was anhydrous ethanol, and the ball-milling time was 3 h; secondary calcination was carried out under argon atmosphere, the calcination temperature was 800° C., and the calcination time was 6 h to obtain the lithium lanthanum zirconium oxide-coated modified lithium titanate hollow microspheres.

[0107] Comparative Example 5 (without adding stearic acid):

[0108] In step (2) of comparative example 5, stearic acid was not added during the preparation of SiO2@lithium titanate microspheres, and the rest was the same as in example 1.

[0109] The performance of the lithium titanate batteries in the above examples and comparative examples was tested, and the discharge capacity, rate discharge and cycle life were evaluated in the range of 1.5 to 2.8 V. The results are shown in Tables 1 and Figures 1 to 3 as shown in .

[0110] Table 1: Lithium titanate battery performance test results.

[0111]

[0112]

[0113] From Table 1 and Figures 1 to 3 It can be seen that the negative electrode active material of Examples 1 to 3 adopts the double-shell lithium titanate-lithium lanthanum zirconium oxide composite hollow microspheres prepared by the present invention, and the battery has good rate performance and a high capacity retention rate during high rate charge and discharge.

[0114] In the negative electrode active material in Comparative Example 1, the carbon coating layer is directly coated on the surface of the lithium titanate hollow microspheres without providing an LLZO layer. The ionic conductivity of the material decreases, resulting in a decrease in the rate performance of the battery compared with that in Example 1, and a decrease in the cycle performance at high rates.

[0115] In the negative electrode active material in Comparative Example 2, the double-shell lithium titanate-lithium lanthanum zirconium oxide composite hollow microspheres are not coated with a carbon coating layer, and the electronic conductivity of the material is low, which also leads to a decrease in the rate performance and cycle performance of the battery at high rates.

[0116] In Comparative Example 3, the negative electrode active material is not made into hollow microspheres, and the tap density and specific surface area of ​​the material are reduced, resulting in that the initial capacity of the battery and the cycle performance at high rate are reduced compared with those in Example 1.

[0117] In the negative electrode active material of Comparative Example 4, LLZO is directly coated on the surface of the lithium titanate hollow microspheres, there is no gap between LLZO and lithium titanate, and the cycle performance of the battery at a high rate is also reduced.

[0118] In Comparative Example 5, stearic acid is not added during the SiO2@lithium titanate microsphere process, there is no carbon coating on the surface of the lithium titanate shell, and the electronic conductivity of the negative electrode active material decreases; and the porosity of the lithium titanate shell and the LLZO shell decreases, resulting in a decrease in the rate performance and cycle performance of the battery.

Claims

1. An ultra-wide temperature high rate lithium titanate battery, characterized in that: The invention comprises a positive electrode, a negative electrode and an electrolyte; the active material in the negative electrode is a double-shell lithium titanate-lithium lanthanum zirconium oxide composite hollow microsphere, and the preparation method thereof comprises the following steps: (1) Preparation of monodisperse SiO2 microspheres: under stirring, add anhydrous ethanol solution of ethyl orthosilicate dropwise into anhydrous ethanol solution of ammonia water, stir and react for 1-2 hours, and separate the product to obtain monodisperse SiO2 microspheres; (2) Preparation of SiO2@lithium titanate microspheres: Monodisperse SiO2 microspheres were added to anhydrous ethanol, and stearic acid was added. After uniform dispersion, tetrabutyl titanate was added. LiOH aqueous solution was added dropwise to the system under stirring, and the reaction was continued under stirring for 2-3 hours. The product was separated to obtain SiO2@lithium titanate microspheres. (3) Preparation of SiO2@Lithium Titanate@SiO2 Microspheres: Add SiO2@Lithium Titanate Microspheres to anhydrous ethanol, disperse them evenly, and then add ethyl orthosilicate; add anhydrous ethanol solution of ammonia water to the system under stirring, stir and react for 1-2 hours, and separate the product to obtain SiO2@Lithium Titanate@SiO2 Microspheres; (4) Preparation of SiO2@lithium titanate@SiO2@LLZO microspheres: Dissolve LiNO3, La(NO3)3, and ZrO(NO3)2 in deionized water, add SiO2@lithium titanate@SiO2 microspheres, disperse them evenly, then add citric acid and ethylene glycol, stir and react at 100-120°C for 12-24h to obtain SiO2@lithium titanate@SiO2@LLZO microspheres; (5) Primary calcination: calcining SiO2@lithium titanate@SiO2@LLZO microspheres at 700-900°C for 4-6 hours under an inert atmosphere to obtain a primary calcined material; (6) Removing the template: After the pre-sintered material is cooled, it is added into a sodium hydroxide solution and stirred at 80-90°C for 4-6 hours. The product is separated, washed and dried to obtain double-shell hollow microspheres. (7) Carbon coating: After the double-shell hollow microspheres are mixed with glucose and ball-milled, they are subjected to secondary calcination in an inert atmosphere at a calcination temperature of 700-900° C. for a calcination time of 5-8 h to obtain the double-shell lithium titanate-lithium lanthanum zirconium oxide composite hollow microspheres.

2. The ultra-wide temperature high rate lithium titanate battery according to claim 1, characterized in that: The volume ratio of ethyl orthosilicate, ammonia water and anhydrous ethanol added in step (1) is 1:15-25:90-100.

3. The ultra-wide temperature and high rate lithium titanate battery according to claim 1, characterized in that: In step (2), the mass ratio of monodisperse SiO2 microspheres to tetrabutyl titanate is 1:8-10; the mass ratio of stearic acid to tetrabutyl titanate is 1:45-55; and the molar ratio of tetrabutyl titanate to LiOH is 5:4.2-4.

6.

4. The ultra-wide temperature and high rate lithium titanate battery according to claim 1, characterized in that: In step (3), the mass ratio of SiO2@lithium titanate microspheres to tetraethyl orthosilicate is 1:3-5, and the volume ratio of tetraethyl orthosilicate to ammonia water is 1:5-7.

5. The ultra-wide temperature and high rate lithium titanate battery according to claim 1, characterized in that: In step (4), the molar ratio of LiNO3, La(NO3)3, and ZrO(NO3)2 is 7.5~7.7:3:2; the ratio of the mass of the added SiO2@lithium titanate@SiO2 microspheres to the total mass of the nitrate is 0.3~0.5:1; the ratio of the mass of citric acid and ethylene glycol to the total mass of the nitrate is 1.2~1.5:0.8~1:

1.

6. The ultra-wide temperature and high rate lithium titanate battery according to claim 1, characterized in that: The concentration of the sodium hydroxide solution in step (6) is 2-5 mol / L.

7. The ultra-wide temperature and high rate lithium titanate battery according to claim 1, characterized in that: In step (7), the mass ratio of double-shell hollow microspheres to glucose is 1:0.15-0.25, the ball milling medium is anhydrous ethanol, and the ball milling time is 2-4 hours.

8. The ultra-wide temperature and high rate lithium titanate battery according to claim 1, characterized in that: The active material in the positive electrode is selected from one or two of lithium iron manganese phosphate and NCM ternary materials.

9. The ultra-wide temperature and high rate lithium titanate battery according to claim 1, characterized in that: The electrolyte includes lithium salt and carbonate organic solvent.

10. The ultra-wide temperature and high rate lithium titanate battery according to claim 9, characterized in that: The concentration of lithium salt in the electrolyte is 1-2 mol / L.

Citation Information

Patent Citations

  • Preparation method of spherical hollow lithium titanate / graphene composite material as lithium battery negative material

    CN104617270A

  • Double-coated lithium battery positive electrode material and preparation method thereof

    CN112670514A